THE EXTENSIVE AND COHESIVE READING IN A FOREIGN LANGUAGE / LECTURE APPROFONDIE ET COHERENTE DANS UNE LANGUE ETRANGERE - Nicoleta Florina MINCǍ (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2022)
The purpose of our paper is to highlight that extensive and cohesive reading has an important role to play in EFL learning. Extensive reading broadens and increases the students’ vocabulary exposing them to various registers of the target language. Cohesion refers to the relations of meaning that exist within the text and that define it as a text. The teacher can help the students use various cohesive chains, which form the backbones of different types of texts. He also needs to monitor each student’s reading and offer guidance and encouragement. Besides, the selection of the reading material should be appropriate to the learners’ linguistic level and their cultural particulars.